Sociosexuality, Morningness–Eveningness, and Sleep Duration - Christoph Randler (SAGE Open, 2016)
Morningness–eveningness is the preference for different times of day for activity and sleep. Here, we addressed the effects of sleep behavior and morningness–eveningness on sociosexuality. Three hundred students ( M age = 22.75 years, with 95% between 18 and 28) participated online, answering questions about morningness–eveningness (rMEQ [Reduced Morningness–Eveningness Questionnaire]), midpoint of sleep on free days (MSF), sleep duration, and the Sociosexuality Orientation Inventory–Revised (SOI-R). The SOI-R contains three subscales, Behavior, Attitude, and Desire. Evening orientation and short sleep duration were related to a higher total SOI-R and to the three subscales. Based on the linear models, the strongest effect on sociosexuality was produced by gender (27% explained variance) while age accounted for 6% of variance. Nonadditive variance explained by sleep–wake behavior was 7% (MSF), 4% (sleep duration), and 4% (rMEQ scores; 3% rMEQ-based typology). Older age was related to less-restricted sociosexuality, and men were less restricted than women in Attitude and Desire. Sleep duration and rMEQ scores were associated with Attitude and Desire; but only MSF was significantly related to Behavior. The data show that sleep–wake variables are associated with sociosexuality, with evening orientation and shorter sleep duration being related to a less-restricted sociosexuality.